2011
DOI: 10.1186/1471-2121-12-45
|View full text |Cite
|
Sign up to set email alerts
|

Masked mRNA is stored with aggregated nuclear speckles and its asymmetric redistribution requires a homolog of mago nashi

Abstract: BackgroundMany rapidly developing systems rely on the regulated translation of stored transcripts for the formation of new proteins essential for morphogenesis. The microspores of the water fern Marsilea vestita dehydrate as they mature. During this process both mRNA and proteins required for subsequent development are stored within the microspores as they become fully desiccated and enter into senescence. At this point microspores become transcriptionally silent and remain so upon rehydration and for the rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…The cytohistological assays we conducted revealed that normal degradation and absorption of both endothecium and tapetum were inhibited, thus leading to defects in pollen maturation and morphology. Defects in pollen development were also observed in hapless1 (atmago) and AtMAGO-RNAi plants in Arabidopsis (Johnson et al, 2004;Park et al, 2009) and in the knockdowns of MvMAGO in M. vestita (van der Weele et al, 2007;Boothby and Wolniak, 2011). However, the transgenic rice plants in our study did not show any defects in floral meristem and seed development, as were observed in Arabidopsis (Park et al, 2009).…”
Section: Functional Divergence Of Mago and Y14 Duplicated Gene Pairs supporting
confidence: 57%
See 1 more Smart Citation
“…The cytohistological assays we conducted revealed that normal degradation and absorption of both endothecium and tapetum were inhibited, thus leading to defects in pollen maturation and morphology. Defects in pollen development were also observed in hapless1 (atmago) and AtMAGO-RNAi plants in Arabidopsis (Johnson et al, 2004;Park et al, 2009) and in the knockdowns of MvMAGO in M. vestita (van der Weele et al, 2007;Boothby and Wolniak, 2011). However, the transgenic rice plants in our study did not show any defects in floral meristem and seed development, as were observed in Arabidopsis (Park et al, 2009).…”
Section: Functional Divergence Of Mago and Y14 Duplicated Gene Pairs supporting
confidence: 57%
“…The Arabidopsis (Arabidopsis thaliana) AtMAGO gene is required for pollen grain development, and its knockout is lethal (Johnson et al, 2004;Park et al, 2009). Mutation of MvMAGO disrupts spermatogenesis in Marsilea vestita (van der Weele et al, 2007;Boothby and Wolniak, 2011). Besides, plant MAGO genes also seem to have broad roles in the growth and development of other plant organs.…”
mentioning
confidence: 99%
“…S6): When desiccated membranes are rehydrated, they become transiently leaky, making the uptake of large macromolecules possible (29), which has been exploited previously to introduce large nucleic acids and drugs into the cytoplasm of rehydrating anhydrobiotic cells (30)(31)(32). In addition, when tardigrades, rotifers, and other anhydrobionts desiccate, genomic double-stranded breakages and other damage are induced (19,33,34), and there appear to be robust mechanisms for repairing this damage (19,34).…”
mentioning
confidence: 99%
“…Our early work showed that at most a small amount of new transcription might be required for late stages of development when mature spermatozoids emerge from the spore wall [Hart and Wolniak, ; Klink and Wolniak, ]. The transcripts are stored in the dry spore within nuclear speckles as partially processed pre‐mRNAs [Boothby and Wolniak, ]. During gametophyte development, the stored pre‐mRNAs become unmasked, spliced, polyadenylated, and translated in a precise spatio‐temporal relationship to form motile spermatozoids [Tsai et al, ; Boothby and Wolniak, ; Boothby et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…The transcripts are stored in the dry spore within nuclear speckles as partially processed pre‐mRNAs [Boothby and Wolniak, ]. During gametophyte development, the stored pre‐mRNAs become unmasked, spliced, polyadenylated, and translated in a precise spatio‐temporal relationship to form motile spermatozoids [Tsai et al, ; Boothby and Wolniak, ; Boothby et al, ]. Since development is post‐transcriptionally regulated, we suspected that transcripts encoding proteins required for cell division would be available early in development, when the mitotic division cycles are occurring, and that those involved in spermatid differentiation and ciliogenesis would become available during later phases of spermiogenesis.…”
Section: Introductionmentioning
confidence: 99%